(Bio)nanosystems based on quantum dots, plasmonic or magnetic nanoparticles - Coutinho, Paulo J. G. (2016)
In this talk, the development of quantum dots, plasmonic and magnetic nanoparticles at CFUM is described, as well as their applications in the ongoing research in Bionanosystems. (Communication in the "Nanoscience and Nanotechnology" panel).